Molecular epidemiology of Paracoccidiodes spp. recovered from patients with paracoccidioidomycosis in a teaching hospital from Minas Gerais State of Brazil - Andrade-Silva, Juliana; Andrade-Silva, Leonardo Euripedes; Paes, Hugo Costa; Alves, Lucas; Rosa, Adair; Tenório, Bernardo Guerra; Ferreira, Marcelo Simão; Felipe, Maria Sueli Soares; Teixeira, Marcus de Melo; Silva-Vergara, Mario León (PLOS Neglected Tropical Diseases, 2021)
Introduction Paracoccidioidomycosis (PCM) is caused by several species of the Paracoccidioides genus which can be differentiated by interspecific genetic variations, morphology and geographic distribution. Intraspecific variability correlation with clinical and epidemiological aspects of these species still remains unclear. This study aimed to sequence the loci GP43, exon 2 and ARF of 23 clinical isolates of Paracoccidioides spp. from patients in the Southeast Region of Brazil. Methodology and main findings GenBank was used to compare the present (23) with previous described sequences (151) that included ARF and GP43. It was identified a high polymorphism rate among the 23 isolates in comparison to the other 151. Among the isolates, 22 (95.66%) were S1/P. brasiliensis and 1 (4.34%) was identified as PS2/P. americana. A total of 45 haplotypes were found as follows: 19 from S1/P. brasiliensis (13 from the present study), 15 from P. lutzii, 6 from PS2/P. americana (1 from the present study), 3 from PS3/P. restrepiensis and 2 from PS4/P. venezuelensis. Moreover, exclusive haplotypes according to clinical origin and geographical area were found. S1/P. brasiliensis (HD = 0.655 and K = 4.613) and P. lutzii (HD = 0.649 and K = 2.906) presented the highest rate of polymorphism among all species, from which 12 isolates of the present study were clustered within S1b/P. brasiliensis. The GP43 locus showed a higher variability and was found to be the main reason for the species differentiation. Conclusions The results herein decribed show a high intraspecific genetic variability among S1/P. brasiliensis isolates and confirm the predominance of this species in the Southeast region of Brazil. The finding of exclusive haplotypes according to clinical origin and geographical area would suggest correlation between the molecular profile with the clinical form and geographic origin of patients with PCM.